Pengembangan Bahan Ajar Berbasis Literasi Dan Numerasi Dengan Model STAD Untuk Meningkatkan Motivasi Dan Penalaran Siswa SMP (Development of Teaching Materials Based on Literacy and Numeracy Using the STAD Model to Increase the Motivation and Reasoning of - Suyatno, Rendra; Hindriana, Anna Fitri (Peneliti.net, 2023)
This research is motivated by the scientific reasoning abilities and motivation of students currently still low. The low reasoning ability and motivation of students is caused by a lack of teachers in applying reasoning abilities in learning in the classroom. To overcome these problems, literacy and numeracy teaching materials with STAD are one of the learning efforts to improve students' scientific reasoning abilities through contextual learning and discovery learning. This study aims to determine students' scientific reasoning abilities through the development of literacy and numeracy teaching materials with STAD. This research method is a research and development method or Research and Development (R & D) to develop the media used for literacy and numeracy teaching materials with STAD. The research sample consisted of two classes consisting of an experimental class and a control class. The results showed a significant increase in students' scientific reasoning abilities in the experimental class after the implementation of literacy and numeracy teaching materials with STAD when compared to the control class using conventional teaching materials, because the use of literacy and numeracy teaching materials with STAD is an interesting thing for students so that they become more enthusiastic and enthusiastic in learning. The development of literacy and numeracy teaching materials with STAD is very well implemented at SMPN 2 Ciwaringin for the science learning process in substances and their changes, especially if SMPN 2 Ciwaringin has limited tools and materials as well as a laboratory or SMPN 2 Ciwaringin.